The endogeneity of domestic violence: understanding women empowerment through autonomy - Fakir, Adnan M.S.; Anjum, Anika; Bushra, Fabiha; Nawar, Nabilah (© 2016 Elsevier Ltd., 2016)
This article was published in World Development Perspectives [©2016 Elsevier Ltd.] and the definite version is available at: http://www.sciencedirect.com/science/article/pii/S2452292916300431 The article website is at: http://www.journals.elsevier.com/world-development-perspectives